Revolution again in Kyrgyzstan : forward to the past? - Schmitz, Andrea (2021)
Zusammenfassung: Kyrgyzstan's presidential election and constitutional referendum on 10 January 2021 represent the provisional endpoint of a series of violent episodes that has gripped the country since October 2020. The victory of the populist Sadyr Japarov and approval for his plan to reintroduce a presidential system of government prepares the ground for a dismantling of democratic principles and rule of law, so that politically Kyrgyzstan is set to look more like its Central Asian neighbours. A new constitution is in preparation. The draft bears the portents of a neo-traditional roll-back that rebuffs a young generation demanding more democracy and rule of law, and has the potential to deeply polarise the nation